Man, Culture, History - Jankauskas, Skirmantas (Problemos, 1984)
It was at the end of the 19th and the beginning of the 20th centuries that Westem Europe was experiencing some cultural crisis. H. Ortega y Gasset, a Spanish philosopher, .found the crisis to be an inevitable consequence of overestimating the potentialities of reason. To his mind, reason was raised to the level of the highest principle of human life as far back as Antiquity. This initiated autonomization and, later, objectification of culture. Having lost touch with spontaneity of life, culture was stiffening and, instead of stimulating the manifestation of life, was turning into an obstacle. Tue following solution is taken by H. Ortega y Gasset: reason must be subordinated to life while culture thereby has to be life-giving. An attempt at an historical reconstruction of the solution by R Ortega y Gasset is made as well as an alternative approach towards the problem under consideration is suggested in the article.